사료작물-벼 작부체계가 조생종 벼의 생육과 미질 특성 및 토양의 화학적 특성에 미치는 영향 - 오서영; Seo Young Oh; 오성환; Seong Hwan Oh; 서종호; Jong Ho Seo; 최지수; Jisu Choi (Korean journal of crop science, 2021)
To select rice (Oryza sativa L.) cultivars suitable for forage-rice double cropping system, the growth and grain quality of four early maturing rice cultivars (Joun, Jopyeong, Haedamssal, and Unkwang), and the chemical properties of soils were investigated under single- (fallow-rice) and forage-rice double-cropping systems in paddy fields in Miryang, southern Korea. The soil where two forage crops [Italian ryegrass (Lolium multiflorum Lam.) and oat (Avena sativa L.)] were cultivated during winter had a slightly lower pH; an increase in total nitrogen (T-N), K, Ca, and Na contents; and a slight decrease in organic matter and available P2O5 contents, compared with the soil fallowed during winter. This shows that the chemical properties of paddy soils can be improved by winter forage cropping. At the heading stage, the culm length, panicle length, panicle number, and leaf color of all cultivars, except for Haedamssal, were generally higher under double-cropping than under single-cropping. For Haedamssal, the culm length and leaf color did not differ between the cropping systems, but the panicle length was slightly shortened and its panicle number increased under double-cropping. After harvest, the yield of milled rice decreased for all cultivars except Haedamssal, but increased in Haedamssal under double-cropping. The head rice rate was slightly higher under double cropping, particularly in Jopyeong and Haedamssal, than under single-cropping. The protein content of milled rice under double cropping was higher and its amylose content was similar or slightly lower compared to those of rice under single cropping, resulting in decreased Toyo values for rice under double-cropping. The pasting temperature did not differ significantly between the cropping systems. However, Haedamssal had a low pasting temperature but a high Toyo value under double cropping, compared to the other three cultivars, suggesting that its palatability is relatively high. Furthermore, panicle number increased and milled rice yield did not decrease, even under double cropping. Therefore, Haedamssal seems to be the best cultivar for paddy-based double cropping with forage crops.